(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
This paper aims to analyze the industrial profile of the Brazilian State Santa Catarina, the focus is to answer the following question: Is it occurring a process of deindustrialization in the Santa Catarina State? In this sense, were adjusted two Vector Error Correction Models (VEC), with the following dependent variables: exports of manufacturing industry (high intensity, medium high, medium-low and low intensity) of the Santa CatarinaState and the exportations of non-industrial products of this State. The independent variables were real effective exchange rate; price index of commodities; and coefficient of the commercial openness degree. The results indicated that the exports of non-industrial products presented a greater increase than the products by technological intensity. In relation to the imports of the non-industrial products, was noted a much smaller increase than the manufacturing industry products by technological intensity. Considering the VEC estimation, the results indicated that the exchange devaluation doesn ́t stimulates the exports; the commercial openness was extremely damaging to the imports and the variable index of the commodities price presented an opposite sign than the expected. Finally, it is possible to conclude that there are strong evidences of the deindustrialization process in Santa CatarinaState.Keywords: Manufacturing Industry; Exchange Rate;Vector Error Correction.